Assessing Production Efficiency: A Case Study of the Ballast Water Treatment System in a Turkish Maintenance Shipyard - Mentes, Ayhan; Koç, Ender; Güngör, Muhammed Alperen; Ağri, Ümit (Transactions on Maritime Science, 2025)
The installation and implementation of ballast water treatment systems (BWTS) are crucial for protecting marine ecosystems, preserving biodiversity, promoting human health and supporting global economic sustainability. This study evaluates the effectiveness of installing these essential systems, with a focus on enhancing production efficiencies in the manufacture and installation of BWTS pipes. We conducted a detailed assessment at a leading maintenance and repair shipyard in Turkey, guided by a team of experts. The aim was to optimize operational processes by identifying delays and bottlenecks in pipe production and installation. Using Arena Simulation, we pinpointed disruptions and inefficiencies within the production system. Based on this analysis, we developed and executed targeted improvements that led to significant improvements. Notably, the annual output increased from 23 to 41 units, reflecting a 78% increase in productivity. These improvements are of far-reaching importance and provide valuable strategies for increasing production efficiency in any pipe manufacturing. Our findings offer key insights into refining operational processes and boosting productivity in a variety of industrial contexts.